1950s Milwaukee: Race, Class, and a City Divided. (March 2017) - Connell, Tula
Overwhelmingly white and middle class, Milwaukee in the 1950s stood at the brink of rapid demographic change as thousands of African Americans from the U.S. South migrated to the city. From 1950 to 1960, Milwaukee's black population grew from 21, 772 to 62, 458, a 187 percent increase that alarmed many white residents and provided fuel for a race-baiting mayoral campaign against the city's liberal mayor in 1956. But even as the new residents challenged long-held notions of white privilege, their arrival also was not uniformly welcomed by the city's longtime middle- and upper middle-class African American residents, whose classist perspective often aligned with white municipal lawmakers and community and labor leaders. The increased number of low-income African American migrants living in Milwaukee brought into sharp relief the inability of all black Milwaukeeans to secure jobs and decent housing. Furthermore, African American job seekers found little recourse in the local labor movement, with union leaders and members mirroring the city's sociocultural biases. African American migrants faced a combination of racial discrimination and class-based bias built on perceptions that all black migrants were lower skilled, low-income workers who did not fit into the city's "culture, " a euphemism frequently employed to reference "class." This article examines how the response of labor, lawmakers, and the community in 1950s Milwaukee, like Detroit and Chicago in earlier years, set the direction for decades to come.